Detection of Ratanjot in Spices and food Preparations by Reverse Phase Chromatography - Chakraborti, I.; Raghav, S.S.; Lal, kanhaya (Asian Journal of Chemistry, 2010)
In the present work, the author has described the detection of Ratanjot as an adulterant in spices and food preparations by reverse phase chromatography.